2007
DOI: 10.1577/m06-075.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tournaments on the Largemouth Bass Population at Sam Rayburn Reservoir, Texas

Abstract: There have been concerns regarding tournament-related impacts on black bass Micropterus spp. for 40 years, but few studies have quantified those impacts. About 52% of anglers at Sam Rayburn Reservoir (46,356 ha) participate in tournaments, and the annual number of events probably exceeds 300. In 2003, we tagged and released 6,021 largemouth bass M. salmoides to estimate the annual proportion of the population caught and retained by tournament anglers. Tag returns were obtained via creel sampling to avoid nonre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…Exploitation rates of Alabama bass in Allatoona Reservoir were higher than the 3-15% found for populations of largemouth bass in south-eastern USA reservoirs in the 2000s (Slipke et al 2004;Driscoll et al 2007;Fontaine et al 2010;Hysmith et al 2014). However, largemouth bass have been the subject of a rigorous catch-and-release programme for the past three decades (Quinn 1996;Myers et al 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Exploitation rates of Alabama bass in Allatoona Reservoir were higher than the 3-15% found for populations of largemouth bass in south-eastern USA reservoirs in the 2000s (Slipke et al 2004;Driscoll et al 2007;Fontaine et al 2010;Hysmith et al 2014). However, largemouth bass have been the subject of a rigorous catch-and-release programme for the past three decades (Quinn 1996;Myers et al 2008).…”
Section: Discussionmentioning
confidence: 89%
“…Estimates of Z could therefore provide inference about the mortality associated with tournament utilisation on the bass population at Wriggleswade Dam. Similarly, Driscoll et al (2007) found low overall fishing mortality rates associated with bass tournaments at Sam Rayburn Reservoir, Texas, and Allen et al (2004) indicated low population-level impacts of tournaments in the Southern USA. Overall, our results revealed low population-level impacts of tournament mortality, and more studies like this are needed (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Angling tournaments are an increasingly popular recreational activity (Wilde, 2003;Driscoll et al, 2007Driscoll et al, , 2012Schramm and Hunt, 2007) that impose additional stressors on fish populations through their potential for increased removal of fish in localised areas and the continual selection for larger fish by anglers, which may influence population dynamics and ultimately alter the genetic stock structure (Meals and Miranda, 1994;Quinn, 1996;Wilde, 1998Wilde, , 2003Cooke et al, 2000;Wilde and Paulson, 2003). As a result, live fish weigh in and release has long been mandatory in some tournament fisheries, particularly those focussing on black bass (Micropterus) species (Clark, 1983;Schramm et al, 1991;Quinn, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in water bodies such as Sam Rayburn Reservoir in Texas tournaments account for a significant part of total fishing (52% of all anglers participate in competitions; Driscoll et al. ) despite the relatively low relative number of tournament anglers in Texas (<6% of all licensed anglers; Kyle et al. ).…”
Section: Discussionmentioning
confidence: 99%